2001
DOI: 10.1128/jcm.39.10.3727-3732.2001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Susceptibility of 3,051Staphylococcus aureusIsolates from 25 University Hospitals Participating in the European SENTRY Study

Abstract: A total of 3,051 methicillin-susceptible Staphylococcus aureus (MSSA) isolates and methicillin-resistant S. aureus (MRSA) isolates in Europe were compared. MRSA isolates constituted 25% of all isolates and were more prevalent in southern Europe. MRSA isolates appeared to be more prevalent in intensive care units than in outpatient departments. Only a small minority of MSSA isolates were multidrug resistant, whereas the majority of MRSA isolates were multidrug resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
134
1
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(164 citation statements)
references
References 17 publications
14
134
1
15
Order By: Relevance
“…The frequency of infections and outbreaks due to MRSA considerably differs by country. It is extremely high in Japan, where it is around 60% (Otsuki and Nishino, 2000), while in Switzerland and The Netherlands this percentage is approximately 2% (Fluit et al, 2001), and in hospitals of the USA 26.9% of the S. aureus and 71.5% of CNS strains are methicillin resistant .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The frequency of infections and outbreaks due to MRSA considerably differs by country. It is extremely high in Japan, where it is around 60% (Otsuki and Nishino, 2000), while in Switzerland and The Netherlands this percentage is approximately 2% (Fluit et al, 2001), and in hospitals of the USA 26.9% of the S. aureus and 71.5% of CNS strains are methicillin resistant .…”
Section: Discussionmentioning
confidence: 98%
“…Since methicillin-resistant S. aureus (MRSA) was first recognised in England in 1961, MRSA strains have become common aetiologic agents of serious hospital infections in humans throughout the world (Fluit et al, 2001). According to the results of the SENTRY Antimicrobial Surveillance Program, between 1997 and 2000 the incidence of MRSA increased from 23% to 34% in Europe, from 26% to 36% in North America and from 49% to 54% in the AsiaPacific region.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da menor freqüência de resistência de Staphylococcus aureus à linezolida, o achado de resistência associada a este antimicrobiano é preocupante, visto que esta droga tem sido considerada uma das últimas opções terapêuticas para infecções graves causadas por isolados de ORSA, frequentemente multirresistentes 7 . Desta forma, estes resultados sugerem o uso mais restrito da linezolida, a fim de garantir o máximo da sua atividade em infecções mais graves.…”
Section: Altas Taxas De Resistência Individual Entre Os Isolados Deunclassified
“…12 MRSA has become resistant to multiple other antimicrobial agents, including aminoglycosides, fluoroquinolones, tetracyclines and macrolideslincosamides-streptogramins. 13 Various MRSA control strategies have been proposed, ranging from contact precautions and active surveillance to topical treatment and more aggressive policies, such as the Dutch MRSA program. 14,15 A recent prospective study performed in two English ICUs, though, demonstrated no reduction of MRSA cross-infection with isolation/cohorting of MRSA-positive patients.…”
Section: Discussionmentioning
confidence: 99%